Violência contra mulheres nas relações de intimidade: Prevalência das consequências para a saúde - Maria da Conceiçao Clemente Oliveira Teixeira (2022)
Intimate partner violence is characterized by violent actions against a person, perpetrated by his/her former or current partner, regardless of cohabitation. It affects especially women and one of its most relevant outcomes is the health problems associated with the experience of repeated violence. Thus, the main objective of this study is to analyze the prevalence of women's health problems, for whom there was a medical suspicion of being victims of intimate partner violence. The specific objectives are to analyse the prevalence of (a) health risk behaviours; (b) trauma; (c) mental health conditions; (d) somatic diseases. We made a real-world, retrospective, observational, transversal study, based on secondary data analyses of electronic health records and health care register data in patients of the Local Healthcare Unit of Matosinhos (between 2001 and 2021). The identified data were extracted from electronic health records according to the Health Insurance Portability and Accountability Act Safe Harbor Standard. Information was obtained considering the International Classification of Diseases and the International Classification of Primary Care, as well as the clinical notes (according to the previously defined keywords). Considering both information sources, 1676 cases were obtained. This number means that just 2% of the women observed at this Healthcare Unit were suspected of being victims of intimate partner violence, which is far from the known reality. However, through these cases, we were able to prove that all health risk behaviours, trauma cases, mental health conditions and somatic disorders we looked for, present much higher rates than the general population. This is a reason of concern for health professionals who need to detect more precociously these cases of violence to prevent or decrease their related-health outcomes.